2015
DOI: 10.1093/jpids/piv076
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Factors in Mothers' Breast Milk and Their Lack of Association With Rotavirus Vaccine Immunogenicity in Nicaraguan Infants

Abstract: To better understand underlying causes of lower rotavirus vaccine effectiveness in low-middle income countries (LMICs), we measured innate antiviral factors in Nicaraguan mothers' milk and immune response to the first dose of the pentavalent rotavirus vaccine in corresponding infants. No relationship was found between concentrations of innate factors and rotavirus vaccine response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Rotavirus-specific IgA and neutralizing antibody titers tend to be significantly higher in breast milk obtained from mothers in low-income countries (e.g., India and Bangladesh) compared with mothers from high-income countries (e.g., the USA and Sweden) and in the rotavirus high season compared with the low season [23,55,56]. Similarly, higher levels of lactoferrin and lactadherin have been observed in breast milk obtained from Indian and South-African women compared with North-American women [57], although these innate immune factors did not correlate with RotaTeq immunogenicity in a recent study in Nicaragua [58]. In the case of poliovirus, significantly higher IgA titers were documented in breast milk samples from unvaccinated women from Pakistan compared with vaccinated women from Japan or Sweden in the early 1990s [59], and it is likely that similar discrepancies between endemic and nonendemic settings persist today.…”
Section: Breastfeedingmentioning
confidence: 91%
“…Rotavirus-specific IgA and neutralizing antibody titers tend to be significantly higher in breast milk obtained from mothers in low-income countries (e.g., India and Bangladesh) compared with mothers from high-income countries (e.g., the USA and Sweden) and in the rotavirus high season compared with the low season [23,55,56]. Similarly, higher levels of lactoferrin and lactadherin have been observed in breast milk obtained from Indian and South-African women compared with North-American women [57], although these innate immune factors did not correlate with RotaTeq immunogenicity in a recent study in Nicaragua [58]. In the case of poliovirus, significantly higher IgA titers were documented in breast milk samples from unvaccinated women from Pakistan compared with vaccinated women from Japan or Sweden in the early 1990s [59], and it is likely that similar discrepancies between endemic and nonendemic settings persist today.…”
Section: Breastfeedingmentioning
confidence: 91%
“…Yet a study conducted in Nicaragua did not find an association between rotavirus-specific IgA titers in breast milk on the day of infant immunization and the immunogenicity of the pentavalent RV (22). Further, they did not find an association between the innate antiviral factors in breast milk, including lactoferrin, lactadherin, and tenascin-C, and RV responses (57).…”
Section: Observational Clinical Studies Of Maternal Immunity and Rotamentioning
confidence: 93%
“…Tenascin-C (TNC) has also recently become the focus of research as another non-immunological breast milk component that has shown activity against the HIV virus through possible blocking of the HIV-1 envelope and might therefore contribute to breast milk viral neutralizing properties [ 16 ]. Work from Nicaragua failed to show any associations between innate immune factors LF, LA or TNC and seroconversion of infants to pentavalent rotavirus vaccine (RV5) [ 17 ]. This difference in results between Moon and colleagues [ 15 ] and Becker-Dreps and colleagues [ 17 ] shows the need to determine which are key factors in the various settings.…”
Section: Introductionmentioning
confidence: 99%
“…Work from Nicaragua failed to show any associations between innate immune factors LF, LA or TNC and seroconversion of infants to pentavalent rotavirus vaccine (RV5) [ 17 ]. This difference in results between Moon and colleagues [ 15 ] and Becker-Dreps and colleagues [ 17 ] shows the need to determine which are key factors in the various settings.…”
Section: Introductionmentioning
confidence: 99%